Analysis of Factors That Influence Hypertension in Community Ages 20-40 Years in The Work Area of The Habinsaran Public Health Center, Toba Regency - Megawati Sinambela (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Hypertension is often referred to as